A Companion to Federico Fellini, Frank Burke, Marguerite Waller and Marita Gubareva (eds) (2020). Issue 1 (1st January 2021) - Welle, John P.
A Companion to Federico Fellini, Frank Burke, Marguerite Waller and Marita Gubareva (eds) (2020)Hoboken, NJ: Wiley Blackwell, 576 pp., ISBN 978-1-11943-153-4, h/bk, 89.29